The influence of the frontal surface area and swim velocity variation in front crawl active drag - Morais, J.E. (2021)
Purpose The aims of this study were to 1) compare active drag (D-a) calculation between a single land-based measurement of frontal surface area (FSA) and in-water FSA measures obtained at key events of the arm pull (1, right upper-limb catch; 2, right upper-limb insweep; 3, right upper-limb exit and left upper-limb catch; 4, left upper-limb insweep; and 5, left upper-limb exit and right upper-limb catch) at front crawl swimming, and 2) compare mechanical power variables computed based on these two approaches. Methods Seventeen swimmers (11, male; 6, female; 16.15 +/- 0.94 yr old) were recruited. The FSA was measured based on two approaches: (i) nonvariation, that is, assuming a constant value, and (ii) variation, that is, calculated in each key event of the front crawl swim. Active drag based on a nonvariation of the FSA was measured using the Velocity Perturbation method. Active drag based on a variation approach was measured in each key event of the front crawl according to the law of linear motion. Pairedt-test (P <= 0.05), simple linear regression models, and Bland-Altman plots between assessment methods (variation vs nonvariation) were computed. Results The FSA (variation) was higher than when assuming a nonvariation (0.1110 +/- 0.010 vs 0.0968 +/- 0.010 m(2), Delta = 15.69%,t= 4.40,P< 0.001,d= 0.95). Active drag (variation) was also significantly higher than when assuming a nonvariation (88.44 +/- 25.92 vs 75.41 +/- 15.11 N, Delta = 16.09%,t= 3.66,P= 0.002,d= 0.61). Conclusions Besides the FSA, swim velocity also changes during the front crawl arm pull. The variation of both variables had a significant effect on the active drag measurement and consequently on mechanical power and total power input variables.